2021
DOI: 10.3389/fchem.2021.680836
|View full text |Cite
|
Sign up to set email alerts
|

Glycosaminoglycans: From Vascular Physiology to Tissue Engineering Applications

Abstract: Cardiovascular diseases represent the number one cause of death globally, with atherosclerosis a major contributor. Despite the clinical need for functional arterial substitutes, success has been limited to arterial replacements of large-caliber vessels (diameter > 6 mm), leaving the bulk of demand unmet. In this respect, one of the most challenging goals in tissue engineering is to design a “bioactive” resorbable scaffold, analogous to the natural extracellular matrix (ECM), able to guide the process o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 165 publications
(145 reference statements)
1
14
0
1
Order By: Relevance
“…Regarding the importance of GAGs for cytokine and growth factor retention in vessels [reviewed in ( Lepedda et al, 2021 )], we also included GAG staining in our study. We showed that native arteries have a high content in tunica media, while, basically, no GAGs are present in the adventitia.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the importance of GAGs for cytokine and growth factor retention in vessels [reviewed in ( Lepedda et al, 2021 )], we also included GAG staining in our study. We showed that native arteries have a high content in tunica media, while, basically, no GAGs are present in the adventitia.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Hong et al [ 275 ] confirmed the capability of decellularized brain tissue hydrogel to promote the repair of spinal cord injury. Further studies of decellularized tissue hydrogels from dermal [ 276 ], bone [ 277 ], and blood vessels [ 278 ] indicate this strategy is suitable for regenerating various tissue types.…”
Section: Biomimetic Structural Materials and Their Fabricationmentioning
confidence: 99%
“…Vascular reconstruction [ 49,102–117 ] – SDF‐1α, [ 103,104 ] VEGF, [ 102,108–114 ] FGF2, [ 115,116 ] Shh+IL‐10 [ 117 ]…”
Section: Gags: Structure Biological Functions and Biomaterials Applic...mentioning
confidence: 99%